Commitment to a resilient development in the social and community projects: the experience in Centro Habana (Islas, 2021)
The development of sustainable communities starts from the rescue of the intrinsic spirituality of the human being with its living environment and depends on the stimulation of its capacities as an active subject that gives creative answers to the current social and environmental problem, the empowerment of resilience. Cuba suffers from multiple impacts of climate change, adaptation actions need the flow of response at the institutional level and the local self-management. Community projects in Centro Habana are indispensable for the rescue of social and environmental values. The systematization of concrete experiences of sustainable practices makes visible the potential of alternative models and allows articulating and strengthening their proposals for the construction of sustainable and resilient communities.
Keywords: sustainable development; social and environmental projects; resilience